2009
DOI: 10.1111/j.1834-7819.2009.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vibration on pain during local anaesthesia injections

Abstract: Background: The ''gate control'' theory suggests pain can be reduced by simultaneous activation of nerve fibres that conduct non-noxious stimuli. This study investigated the effects of vibration stimuli on pain experienced during local anaesthetic injections. Methods: In a preliminary study, subjects were asked to rate anticipated and actual pain from regional anaesthetic injections in the oral cavity. A second study compared, within subjects, pain from injections with and without a simultaneous vibration stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 15 publications
8
64
0
6
Order By: Relevance
“…In this study the level of pain intensity in intervention group was significantly less than control group and the results showed that the vibrational stimulus can be used to reduce the injection related pain. 27 The findings of two recent studies were in accordance with present research.…”
Section: Discussionsupporting
confidence: 82%
“…In this study the level of pain intensity in intervention group was significantly less than control group and the results showed that the vibrational stimulus can be used to reduce the injection related pain. 27 The findings of two recent studies were in accordance with present research.…”
Section: Discussionsupporting
confidence: 82%
“…13,14 Bu teoriye göre ağrıyı taşıyan sinir lifleri küçük çaplı C tipi sinir lifleridir ve büyük çaplı A liflerinin uyarılmasının, küçük çaplı sinir liflerinin taşıdığı ağrı uyarılarına kapıları kapattığı ve ağrı hissinde azalmaya neden olduğu bildirilmektedir. 15,16 Bunun nedeninin basınç veya titreşim uyarıları ile aktive olan büyük çaplı A-delta liflerinin hızlı ileti yapabilme özelliklerinden dolayı taşıdığı stimülusları üst merkezlere C liflerinden önce iletmesi olduğu söylenmektedir. 16 Teorinin; özellikle beynin somatosensöriyel korteksinin yoğun uyarı aldığı, duyarlılığı yüksek ağız bölgesi için ayrı bir önem kazandığı bildirilmektedir.…”
Section: çOcuklarda Palatal Lokal İnfiltrasyon Anestezisiunclassified
“…15,16 Bunun nedeninin basınç veya titreşim uyarıları ile aktive olan büyük çaplı A-delta liflerinin hızlı ileti yapabilme özelliklerinden dolayı taşıdığı stimülusları üst merkezlere C liflerinden önce iletmesi olduğu söylenmektedir. 16 Teorinin; özellikle beynin somatosensöriyel korteksinin yoğun uyarı aldığı, duyarlılığı yüksek ağız bölgesi için ayrı bir önem kazandığı bildirilmektedir. Titreşim uyarılarının orofasiyal bölgede dental, iskeletsel veya musküler kaynaklı akut veya kronik ağrı-lara karşı ağrı eşiğini yükseltmede etkili olduğu bildirilmiştir.…”
Section: çOcuklarda Palatal Lokal İnfiltrasyon Anestezisiunclassified
See 2 more Smart Citations